Miskonsepsi Pemahaman Materi Bangun Datar Dengan Penerapan Teori Polya Di PGMI 3 UINSU - Annisa Rahmadani; Rora Rizky Wandini (CV. ITTC INDONESIA, 2024)
Mathematics is a symbolic language whose practical function is to express quantitative and spatial relationships, while its theoretical function is to make thinking easier. Mathematics is a field of study that plays an important role as a basis. Misconceptions are misunderstandings or inconsistencies in understanding a concept with the scientific understanding accepted by experts. As is. misconceptions that occur, this can make it possible for students to experience difficulties in solving mathematics problems. One of the factors that influences student problem solving is the student's thinking style, because each student has a unique way of thinking. References, or guidelines from other sciences. A flat shape can be defined as a flat shape that has two dimensions, namely length and width, but no height or thickness. Based on research data from PGMI 3 of the State Islamic University of North Sumatra, it shows that there are several students who experience misconceptions in the work on Bangun Datar. Therefore, it is necessary to conduct this research to analyze differences of opinion in solving mathematical problems on plane shape operations. The approach used in this research is a qualitative approach. The type of research used in this research is descriptive research. The aim of this research is to describe the different forms made by students in solving flat shape problems